POLITICAL CARTOON PARTAI DEMOKRAT DALAM HARIAN KOMPAS: Sholihul Abidin - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2016)
The news which is presented variedly is a construction of a social reality. The society then interprets thenews in society’ s point of view freely. Political cartoon in a column ‘ oom pasikom’ of daily news ‘ Kompas’brings out the idea to give a simultaneous interpretation to the conflict of Demokrat party. Known from theCharles Sanders Peirce’ s semiotic theory and Lewis A Coser’ s conflict theory that happened to Demokratparty is an internal conflict. The Conflict was started from the uncovering of corruption which involved AnasUrbaningrum as one of the high-powered person in this party. He was suspected the case of corruption ofHambalang Sport Center project by KPK. Then Anas Urbaningrum was stood down from his function byDemokrat party on behalf of SBY. The culminating point of internal conflict is when Anas Urbaningrum andhis endorsement fought back SBY. Visualized in caricature in column ‘oom pasikom’, published in March2nd, 2013, he revealed his anger by threatening to open up on a charge of his case. He threatened to divulgethe bill out of Century Bank case which was under the KPK investigation. Based on the Lewis A Coser’ sopinion, the conflict between Anas Urbaningrum and SBY in Demokrat party was as a big bang from aninternal conflict because in term of intimate relationship in Demokrat party was possible to their wholepersonality be seen.